Correlation between Left main artery diameter derived by Finet’s Law and direct angiographic quantitative coronary dimension analysis - Shaha, Kunal Bikram; Adhikari, Ashok; Safi, Sajjad; Shakya, Avisesh; Shrestha, Sanjaya Kumar (Nepalese Heart Journal, 2022)
Background and Aims: In the era of left main angioplasty, the aim of this study is to evaluate the applicability of Finet’s law in left main diameter calculation and establish this as a useful feasible alternative  tool to intravascular ultrasound  in the left main intervention.Methods: A total of 164 patients who underwent coronary angiography at PAHS  due to suspicion of coronary artery disease between 1st January 2017 and April 2020 were included. The left main diameter(do-QCA) was calculated using the Quantitative coronary angiographic (QCA) method and correlated with the Left main diameter (do-finets) derived from Finet’s law which takes into account the diameter (d1) of the proximal left anterior descending artery (LAD) and left  circumflex (LCX) diameter (d2) derived from QCA, added together and multiplied by the factor of 0.678 i.e do-finets=0.678(d1+d2).Results: Using the Bivariate Pearson correlation method, do-QCA was found to have a positive correlation with do-finets with a correlation coefficient of (r=0.721) significant at the level of P value 0.01 (2-tailed).Conclusion: The application of Finet’s Law using the QCA method has been found to be a handy feasible alternative tool to intravascular ultrasound   in calculating the left main diameter for the left main intervention where intravascular ultrasound  is not available or economic constraint prevails.